DEVELOPMENT OF MATHEMATICS LEARNING MEDIA BASED ON INTERACTIVE MULTIMEDIA USING ADOBE FLASH CS6 IN THE SUBMISSION OF CULTURAL RULES OF HIGH SCHOOL CLASS XI - Utari Dwi Rahmawati; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Middle school math learning has many diverse issues, including the lack of school facilities and students' interest in learning mathematics courses, which are still low. This study aims to develop media-based interactive multimedia learning math using Adobe Flash CS6 and determine the feasibility of the learning media. This study using ADDIE development research. Subject trials in the development of instructional media consists of the validation test subjects and subjects of research. Subject of validation that media expert lecturers and subject matter experts Ahmad Dahlan University and teacher of mathematics majors of class XI IPA at SMAN 2 Banguntapan. The subjects were students of class XI SMA Negeri 2 Banguntapan. These data collection techniques such as observation, interviews, questionnaires, and tests. Analysis of data using qualitative data analysis is then converted into quantitative. As for the success criteria set out in this research is the minimum feasibility of the product is on the value of Agreed. Product development based on the development of mathematical learning media interactive multimedia using Adobe Flash CS6 on the subject of the enumeration rules High School Class XI Science majors are declared eligible to be used as a medium of learning based on assessment questionnaire with an average score 40.72727273 with the agreed categories. Based on these assessments, the multimedia learning of mathematics is fit for use as a medium of learning.